Design of a Narrow Bandwidth Bandpass Filter Using Compact Spiral Resonator with Chirality - Weiping Li; Zongxi Tang; Xin Cao (Active and Passive Electronic Components)
In this article, a compact narrow-bandpass filter with high selectivity and improved rejection level is presented. For miniaturization, a pair of double negative (DNG) cells consisting of quasi-planar chiral resonators are cascaded and electrically loaded to a microstrip transmission line; short ended stubs are introduced to expand upper rejection band. The structure is analyzed using equivalent circuit models and simulated based on EM simulation software. For validation, the proposed filter is fabricated and measured. The measured results are in good agreement with the simulated ones. By comparing to other filters in the references, it is shown that the proposed filter has the advantage of skirt selectivity and compact size, so it can be integrated more conveniently in modern wireless communication systems and microwave planar circuits.